2017
DOI: 10.1530/ec-17-0159
|View full text |Cite
|
Sign up to set email alerts
|

HIIT produces increases in muscle power and free testosterone in male masters athletes

Abstract: High-intensity interval training (HIIT) improves peak power output (PPO) in sedentary aging men but has not been examined in masters endurance athletes. Therefore, we investigated whether a six-week program of low-volume HIIT would (i) improve PPO in masters athletes and (ii) whether any change in PPO would be associated with steroid hormone perturbations. Seventeen male masters athletes (60 ± 5 years) completed the intervention, which comprised nine HIIT sessions over six weeks. HIIT sessions involved six 30-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 36 publications
4
29
2
2
Order By: Relevance
“…This may indicate that aerobic HIIT could be effective in increasing leg muscle strength. This is in line with HIIT research in healthy populations which demonstrated an increase in muscle strength following a HIIT cycling intervention (Herbert et al, 2017;Wright et al, 2016). As working muscles at a higher intensity produces greater increases in strength (Garber et al, 2011), the increase in strength from HIIT is likely induced from cycling at a higher workrate during the high intensity intervals, compared to continuous moderate intensity training.…”
Section: Mssupporting
confidence: 83%
“…This may indicate that aerobic HIIT could be effective in increasing leg muscle strength. This is in line with HIIT research in healthy populations which demonstrated an increase in muscle strength following a HIIT cycling intervention (Herbert et al, 2017;Wright et al, 2016). As working muscles at a higher intensity produces greater increases in strength (Garber et al, 2011), the increase in strength from HIIT is likely induced from cycling at a higher workrate during the high intensity intervals, compared to continuous moderate intensity training.…”
Section: Mssupporting
confidence: 83%
“…A further issue is the heterogeneity of exercise training design. When two studies used the same exercise intervention, for the same duration, free-T and TT responses were remarkably similar considering sedentary older men were compared to masters athletes (Hayes et al, 2017a; Herbert et al, 2017a). As such, it is possible the exercise intervention specifics (volume, intensity, frequency, etc.)…”
Section: Discussionmentioning
confidence: 92%
“…The two included interval training studies displayed a positive testosterone SDM, with both investigations coming from the same research group (Hayes et al, 2017a; Herbert et al, 2017a). This group used the same high intensity interval training (HIIT) in both studies, which consisted of 6 × 30 s sprints at 40% peak power output (~130% peak oxygen uptake) interspersed with 3 min rest.…”
Section: Discussionmentioning
confidence: 99%
“…The high-volume and high-intensity protocols with short rest intervals between sets tended to lead to greater hormonal changes (Kraemer and Ratamess, 2005 ). Previous studies have reported a significant increase in testosterone levels after high-intensity exercises in runners and master athletes of various modalities (Herbert et al, 2017 ; Nuuttila et al, 2017 ). Women did not present significant chronic testosterone and cortisol changes (Poderoso et al, 2019 ).…”
Section: Discussionmentioning
confidence: 94%